2016
DOI: 10.2174/1389200217666151210142051
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and Cytochrome P450 Interactions

Abstract: Biotransformation via a hydrolytic pathway is the major route of endocannabinoid metabolism and the deactivation of substrates is characteristic, in contrast to the minor oxidative pathway via CYP involved in the bioactivation reactions. Phytocannabinoids are extensively metabolized by CYPs. The enzymes CYP2C9, CYP2C19, and CYP3A4 catalyze most of their hydroxylations. Similarly, CYP represents a major metabolic pathway for both synthetic cannabinoids used therapeutically and drugs that are abused. In vitro ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
155
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(163 citation statements)
references
References 203 publications
3
155
0
5
Order By: Relevance
“…11,22 Among cytochrome P450 (CYP) enzymes, CYP3A4 was found to be the major CYP enzyme responsible for the oxidative metabolism of SCs; and CYP2C9, CYP2C19 and CYP1A2 seem to have contributions. [31][32][33] Besides, SCs and their basic molecules were shown to be capable of inhibiting CYP1A. 34 Research of Borini et al 14 on C use revealed that serum AST, ALT and AP levels were increased without any correlation with the amount or duration of marijuana consumption.…”
Section: Discussionmentioning
confidence: 99%
“…11,22 Among cytochrome P450 (CYP) enzymes, CYP3A4 was found to be the major CYP enzyme responsible for the oxidative metabolism of SCs; and CYP2C9, CYP2C19 and CYP1A2 seem to have contributions. [31][32][33] Besides, SCs and their basic molecules were shown to be capable of inhibiting CYP1A. 34 Research of Borini et al 14 on C use revealed that serum AST, ALT and AP levels were increased without any correlation with the amount or duration of marijuana consumption.…”
Section: Discussionmentioning
confidence: 99%
“…13 There are a range of other possible targets for CBD, which may be relevant to its antiseizure and other pharmacologic effects. 17 There are likely to be active metabolites with both molecules. Both, however, have similar effects on rodent seizure models.…”
Section: Cannabinoids For Epilepsymentioning
confidence: 99%
“…Kannabinoidy są metabolizowane przez wątrobę za pomocą cytochromu p450 [50]. Zarówno CBD, jak i THC hamują szlak cytochromu P450, szczególnie izoenzymy CYP3A4, CYP2C.…”
Section: Patofizjologia Układu Kannabinoidowegounclassified
“…Zarówno CBD, jak i THC hamują szlak cytochromu P450, szczególnie izoenzymy CYP3A4, CYP2C. CBD dodatkowo ma wpływ hamujący na działanie innych izoenzymów jak 2D6, 1A2, 2B6 [50]. Powszechnie wiadomo, że CYP3A4, CYP2C są pobudzane przez karbamazepinę, topiramat, fenytoinę i kwas walproinowy.…”
Section: Patofizjologia Układu Kannabinoidowegounclassified